1997
DOI: 10.1038/ki.1997.31
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic identification of families with juvenile nephronophthisis type 1: Rate of progression to renal failure

Abstract: Familial juvenile nephronophthisis (NPH), an autosomal recessive cystic disease of the kidney, is the most common genetic cause of end-stage renal disease (ESRD) in the first two decades of life. A gene locus for nephronophthisis type 1 (NPH1) has been mapped by linkage analysis to chromosome 2q13. We performed a haplotype analysis in 16 NPH families with at least two affected patients with the typical history, clinical signs and histology of NPH using microsatellite markers of the NPH1 genetic region. By demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 19 publications
1
62
0
1
Order By: Relevance
“…Infantile NPHP, which is characterized by mutations in NPHP2/inversin, leads to ESKD between birth and age 3 yr (17,23). In a study conducted in 46 children who had juvenile NPHP type 1 caused by mutations in the NPHP1 gene, a serum creatinine of 6 mg/dl was reached at a median age of 13 yr (range 4 to 20 yr) (6,22). Similarly, the median age of ESKD in patients with mutations in the NPHP5 gene was 13 yr (20).…”
Section: Nephronophthisis: a Frequent Genetic Cause Of Kidney Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Infantile NPHP, which is characterized by mutations in NPHP2/inversin, leads to ESKD between birth and age 3 yr (17,23). In a study conducted in 46 children who had juvenile NPHP type 1 caused by mutations in the NPHP1 gene, a serum creatinine of 6 mg/dl was reached at a median age of 13 yr (range 4 to 20 yr) (6,22). Similarly, the median age of ESKD in patients with mutations in the NPHP5 gene was 13 yr (20).…”
Section: Nephronophthisis: a Frequent Genetic Cause Of Kidney Failurementioning
confidence: 99%
“…In NPHP, chronic renal failure develops within the first three decades of life (7,22,23). Infantile NPHP, which is characterized by mutations in NPHP2/inversin, leads to ESKD between birth and age 3 yr (17,23).…”
Section: Nephronophthisis: a Frequent Genetic Cause Of Kidney Failurementioning
confidence: 99%
“…16,17,23 Previous studies have not revealed any clinical or histological features that would allow discrimination between deletion-positive and deletion-negative patients. 25 In this study we found three clinical presentations of nephronophthisis. When comparing the patients with deletions in Group I with patients of Group II, both representing recessive nephronophthisis, we found a statistically significant difference in the ages at the first symptoms, the time of diagnosis and the beginning of the dialysis treatment (Table 4).…”
Section: Discussionmentioning
confidence: 77%
“…Extra-renal organ involvement is absent. The clinico-pathological picture is similar to that seen in classic JN, an autosomal recessive disease manifesting earlier in life (age 10±20) [Hildebrandt et al, 1997a]. The gene for JN, called nephrocystin, has been recently identi®ed on chromosome 2q13 [Hildebrand et al, 1997b].…”
Section: Discussionmentioning
confidence: 94%